Timing of Dysphagia Screening in Alzheimer's Dementia. Issue 3 (6th June 2019) - Özsürekci, Cemile; Arslan, Selen Serel; Demir, Numan; Çalışkan, Hatice; Şengül Ayçiçek, Gözde; Kılınç, Hasan Erkan; Yaşaroğlu, Ömer Faruk; Kızılarslanoğlu, Cemal; Tuna Doğrul, Rana; Balcı, Cafer; Sümer, Fatih; Karaduman, Ayşe; et al.
Abstract: Background: Dysphagia is an important and frequent symptom in Alzheimer's dementia (AD). We hypothesized that dysphagia could be seen in the early stages of AD and sarcopenia presence rather than the severity of the AD affecting dysphagia. The main aim of this study was to investigate swallowing functions in AD patients according to stages. The second aim was to investigate the correlation between sarcopenia and dysphagia in AD. Methods: This study involved 76 probable AD patients. For all participants, diagnosis of sarcopenia was based on definitions from the revised version of European Working Group on Sarcopenia in Older People at 2018. Dysphagia symptom severity was evaluated by the Turkish version of the Eating Assessment Tool, a videofluoroscopic swallowing study (VFSS) was performed for instrumental evaluation of swallowing. The patients were divided into 3 groups according to the clinical dementia rating (CDR) scale as CDR 1 (mild dementia), CDR 2 (moderate dementia), and CDR 3 (severe dementia). Swallowing evaluation parameters were analyzed between these groups. Results: Mean age was 78.9 ± 6.4 years, and 56.4% were female. Twenty‐six patients had mild dementia, 31 patients had moderate dementia, 19 patients had severe dementia (CDR 3). We found that sarcopenia rates were similar between AD stages according to CDR in our study population and dysphagia could be seen in every stage of AD. In a multivariate analysis, polypharmacy and sarcopenia were found to be independently associated factors for dysphagia, irrespective of stage of AD (OR: 6.1, CI: 1.57‐23.9, P = 0.009; OR: 4.9, CI: 1.24‐19.6, P = 0.023, respectively). Conclusion: Aspirations may be subtle so that AD patients and caregivers may not be aware of swallowing difficulties. Therefore, all AD patients, especially those who have polypharmacy and/or sarcopenia (probable‐sarcopenia‐severe sarcopenia), should be screened for dysphagia in every stage.